SELF DISCLOSURE AND ACADEMIC STRESS LEVELS IN UNDERGRADUATE NURSING STUDENTS; CORRELATIVE STUDIES - Tamaya Hanisa; Anny Rosiana Masithoh; Ashri Maulida Rahmawati ((IJP) Indonesia Jurnal Perawat, 2024)
Final year students often experience stress in planning, compiling and making final assignments. One way to understand stress is to know the conditions and situations that are being experienced, including self-disclosure. This study aimed to determine the relationship between self-disclosure and the level of academic stress in nursing students. The research method used quantitative with a cross sectional approach. The sampling technique used in this research was simple random sampling with a total of 41 respondents. Data were analyzed using the Spearman rho test. The research results showed a significant correlation between self-disclosure and academic stress in final year Bachelor of Nursing students with a p value (0.000) 0.05. There is a relationship between self-disclosure and the level of academic stress in final year Bachelor of Nursing students